"استراتيجية استهداف التضخم كآلية حديثة لإدارة السياسة النقدية في الدول النامية مع الإشارة الى دولتي: الجزائر والهند الفترة 2001- 2021 " - هدى, أوراق; سامية, بدر الدين; جهاد, عروك (جامعة الوادي - University of Eloued, 2023)
استهداف التضخم هو استراتيجية حديثة للسياسة النقدية تهدف إلى تحقيق مستويات أسعار مستقرة على المدى الطويل، حيث أثبتت هذه السياسة نجاحها في خفض معدلات التضخم في الدول المستهدفة وكذلك استقرار التقلبات في معدلات التضخم، لذلك نتسأل ما إذا نجح البنكين (بنك الجزائر وبنك الاحتياطي الهندي) في تطبيق هذه السياسة، وبالتالي تهدف دراستنا إلى دراسة السياسة النقدية ودورها في استهداف معدلات التضخم في الجزائر والهند خلال الفترة 2001-2020 ولتحقيق هذه الدراسة تم استعراض الجانب النظري للسياسة النقدية والتضخم واستهداف التضخم كما تناولت الدراسة عرض مسار السياسة النقدية في الجزائر والهند وتقييم فاعلية سياسة استهداف التضخم من خلال بعض الادوات المنتهجة من طرف بنك الجزائر وبنك الاحتياطي الهندي ، ولإلمام الجانب النظري قد اعتمدنا على منهج الوصفي اما في جانب التطبيقي اعتمدنا على المنهج التحليلي لتحليل بيانات ومعطيات ..وما يمكن ان نقترحه ونوصي به من خلال درستنا يتطلب أن يكون لبنك الجزائر آليات وبرامج متقدمة للتنبؤ بظاهرة التضخم ونجاح سياسة استهداف التضخم ، من المفترض أن يكون الهدف المركزي لاستهداف التضخم في الهند البالغ 4%هو المفاضلة بين حماية لصالح اصحاب المعاشات من جهة، وأصحاب الدخل الثابت والمدينين والمستثمرين والتوظيف والنمو من جهة أخرى .Inflation targeting is a modern strategy of monetary policy aimed at achieving stable price levels in the long term, as this policy has proven successful in reducing inflation rates in the target countries as well as stabilizing fluctuations in inflation rates, so we wonder if the two banks (Bank of Algeria and Reserve Bank of India) succeeded in applying this policy, and therefore our study aims to study monetary policy and its role in targeting inflation rates in Algeria and India during the period 2001-2020 and to achieve this study Review of the theoretical aspect of monetary policy, inflation and inflation targeting The study also dealt with the presentation of the course of monetary policy in Algeria and India and the evaluation of the effectiveness of the policy of targeting inflation through some of the tools pursued by the Bank of Algeria and the Reserve Bank of India, and for the theoretical side we have relied on the descriptive approach either in the applied side we relied on the analytical approach to analyze data and data. What we can propose and recommend through our study requires that the Bank of Algeria have advanced mechanisms and programs to predict the phenomenon of inflation and the success of the inflation targeting policy, it is assumed that the central goal of targeting inflation in India of 4% is the trade-off between protection in favor of pensioners on the one hand, and fixed income earners, debtors, investors, employment and growth on the other hand.
Keywords: سياسة النقدية، استهداف التضخم، اقتصاد جزائري، اقتصاد هندي.; Monetary policy, inflation targeting, Algeria economy, India economy.